Cassava development: Pilot project in Brazil. Integrated production, processing and commercialization of dry cassava chips for animal consumption: First technical progress report for period ending march 1990 - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1990)
To improve the welfare of the rural poor involved in cassava production in communities in Ceara, NE Brazil, an integrated production, processing, and commercialization project of cassava chips for animal consumption was established. Details are given of site selection, identification of local institutions and financial resources, design and establishment of the pilot project (production and processing technologies, commercialization, organization, training), monitoring of project performance and modification of project design to adapt it to local conditions (characterization of participants in the project as to land tenure and age; definition of size of farmers` organizations; cassava production; sales, wages, and income), and design of the expansion phase to commercial-scale production. (CIAT)